EXPRESSION OF TTF-1, NAPSIN-A, P63 AND P40 IN DIFFERENTIAL DIAGNOSIS OF NON-SMALL CELL LUNG CARCINOMA - Nehad Khan; Talat Mirza; Faisal Faiyaz Zuberi; Muhammad Furqan Bari (ziauddin University, 2024)
Background: Non-small cell lung cancer is classified into different subtypes. It is now mandatory for the histopathologists to classify the NSCLC into its exact classification because of the increase in promising personalized therapy against each of its subtypes. In order to better classify non-small cell lung cancers, the current study evaluates the diagnostic value of p40 and Napsin-A along with the comparison with the conventional markers TTF-1 and P63.   Methods: 147 blinded diagnosis of NSCLC were included and classified based on histological findings. After histological review, all the specimens were stained with the conventional markers and new markers i.e., p40, p63 for squamous-cell-carcinoma (SQC) and TTF-1, Napsin-A for adenocarcinoma (ADC).   Results: Regarding baseline data, out of 147 NSCLC samples, 106 (72.10%) were males and 41 (27.90%) were females with the mean age of the patient was 57.6 years. The new markers combination reclassified tumors as 60 (40.8%) as ADC, 80 (54.4%) as SQC and 7.0 (4.8%) as Transdifferentiated (TD). The sensitivity and specificity of newly proposed markers, that is, Napsin-A and p40 were better than the conventional markers TTF-1 and p63.     Conclusion: Napsin-A and p40 are better markers than presently used markers (TTF-1and p63). These better markers are suggested to be added or the existing markers (TTF-1 and p63) should be preferred by Napsin-A and p40 in the histopathological diagnostic workup of NSCLC.